Quantitative evaluation of PpSP15-LmSTI1 fusion gene expression following transfection with an alphavirus-derived self-amplifying mRNA and conventional DNA vaccine platforms. (October 2021) - Savar, Nastaran Sadat; Vallet, Thomas; Azizi, Masoumeh; Arashkia, Arash; Lundstrom, Kenneth; Vignuzzi, Marco; Niknam, Hamid Mahmoudzadeh
Abstract: New vaccine platforms are crucial to address complex parasitic infections such as cutaneous leishmaniasis. Self-amplifying mRNA (SAM) based vaccines represent the next generation nucleic acid-based platform. In the present study, we compared the expression levels of PpSP15-LmSTI1 fusion gene in BHK-21 cells following transfection with Semliki Forest virus (SFV)-derived SAM, SFV-derived plasmid DNA (pSFV-PD) and conventional plasmid DNA (pcDNA3.1+). PpSP15-LmSTI1 fusion gene expression levels were evaluated at different time points, using quantitative Real-time PCR. All data were validated and normalized by two internal control genes. According to the results, mean values of relative expression were significantly higher for SFV-PD SAM/fusion than pcDNA/fusion and pSFV-PD/fusion at all concentrations and time points. Our results showed that higher levels of PpSp15-LmSTI1 antigen expression could be achieved using a SAM vector than pcDNA and pSFV-PD, making it a valuable and efficient alternative to conventional plasmid DNA-based vaccines against leishmaniasis. Highlights: PpSP15-LmSTI1 relative gene expression is the highest for SAM vector at all concentrations and time points. Higher levels of PpSp15-LmSTI1 expression can be achieved using a SAM vector than pDNA and pSFV-PD plasmid. Lower doses of SAM than pDNA (pcDNA3.1+) are required to express high levels of PpSP15-LmSTI1 antigen in mammalian cells. SAM platform is a valuable and efficient alternative to conventional plasmid DNA-based vaccines against leishmaniasis.